Exploring the Multi-Dimensionality of Tourism Destination Brand Story - Deske W. Mandagi; Donn K. Sondakh (African Journal of Hospitality, Tourism and Leisure, 2022)
The present study reconceptualises the brand story based on market-related cues. Utilizing a mixed-method research design, which involves a qualitative and quantitative approach, this study identifies and confirms the multidimensionality of the destination brand story. In the qualitative stage, the dynamic and complex nature of the destination brand story was explored through participatory and archival netnography on major social media platforms. Subsequently, the thematic content analysis revealed three essential themes: history, myth and legend, and local belief representing the dimensions of the brand story. In the second stage, the brand story dimensionality was confirmed using survey-based data: an exploratory study (n=331) and a confirmatory study (n=253). Subsequently, the result of the structural equation modelling (SEM) uncovered that only two dimensions (i.e., history, myth and legend) significantly form the Wonderful Indonesia brand story. The result provides new insights into the conceptualization of the brand story by identifying a novel and distinct dimensional structure of the brand story. This conceptualization enhances understanding of the complexity and multidimensionality of a destination brand.